“Educated or Warehoused?”: The educational experiences of former NEET and so-called disengaged youth in a Further Education (FE) College in England - Cornish, Carlene (European Journal of Social Science Education and Research, 2025)
RPA (Raising of Participation Age) legislation re-positioned all youth in England to participate in post-16 education and training, the ultimate aim to develop ‘human capital’, i.e. skills, abilities and knowledge (Foucault 2008). However, how does RPA play out in practice with previously NEET and so-called disengaged youth engaged on a Level 1 prevocational course? Empirical research was conducted at a large general further education (FE) college in South East England, named The Site with seven tutors and twenty six students from the 2013-14 and 2014-15 cohorts. Adopting a case study approach, multiple methods of data collection were used, including classroom observations, semi-structured interviews, focus group discussions and document analysis. Key findings problematize education and highlighted complications for marginalised youth that participated in the study. Far from being a straightforward experience for former NEET and disadvantaged youth to gain knowledge and skills whilst at college, conversely, these Level 1 pre-vocational students faced multiple barriers that challenged student efforts to access essential provision in an attempt to improve on previous academic failure. Research findings revealed ‘warehousing’ appeared to be the main purpose of education for these particular students in this study. Distinctly different to stereotypical ideas, these particular students wanted to learn. In a profound way, empirical research highlighted how stringent academic conditions were powerfully used to demarcate access and predetermined which types of youth were permitted on higher levels of study programmes and apprenticeship. This study adopts a social justice framework and therefore advocated for numerous structural and pedagogical changes. Amongst others, the recommendation was made for an overhaul in government and organisational policies on GCSE provision. This study also calls for a sharpened political focus, inviting academic and government debate for a critical re-think and revamp of re-engagement provision - so it is fit for purpose for disadvantaged students.
Keywords: Raising of Participation Age (RPA); Further Education (FE); NEET (not in education, employment or training); Neo-liberalism; Level 1 pre-vocational course, Warehousing, marginalisation; GCSEs; human capital